PEMANFAATAN MEDIA SOSIAL DALAM PENGEMBANGAN UMKM DESA MALALA SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Andhy Saputra; Sarfika Pika; Siti Nur Hazanah; Moh Fadel Rifai; Mohammad Sawir (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The purpose of implementing community service outreach, particularly for MSMEs, is to provide entrepreneurs with knowledge on developing their economic potential. Utilizing social media as a primary tool for marketing MSME products is a necessary action, as social media serves as a platform for product promotion at a relatively low cost, even without cost. Research findings indicate that Malala Village has economic opportunities in the business sector. Most residents transact in that sector. This community service activity makes it easier for MSMEs in Malala Village to create online stores and market their products through marketplace platforms and social media, thereby increasing their income. MSMEs in Malala Village can increase their market reach by establishing online stores. Furthermore, this initiative supports government programs to strengthen the capacity of MSMEs to compete in the market and improve the welfare of the local community.